The role of formal institutions on the longevity of family-owned businesses in Finland - Graham, Alex (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The role of family-owned businesses in national economies cannot be over emphasized and Finland is no exception. It is estimated that 90 percent of the 226,600 companies in Finland are family-owned. These companies contribute immensely to employment and GDP. Despite the immense research conducted in the field of family-owned business, very little has focused on macro environmental level influence on these firms. This thesis examines the impact of formal institutions on the longevity of family-owned business in Finland. The following questions were used in support of the main research problem; What formal institutions affect the family-owned business in Finland? How do these formal institutions affect the family-owned business in Finland? How do these formal institutions affect the longevity of family-owned business in Finland? The theoretical background of the study consists of literature relating to the concept of family-owned business, formal institutions and longevity. The approach of the study is qualitative and exploratory in nature. The empirical data collected for the study was based on expert interviews. An expert on Finnish family-owned businesses and another expert on the formal institution that directly affects the longevity of the Finnish family-owned businesses were interviewed. The findings suggest that though the institutional environment affects all firms the same way regardless of their nature, of particular importance to the longevity of the Finnish family-owned business is the negative effect of the collective agreement system, the financial market regulation and the inheritance tax system in Finland. These regulations have an adverse effect on the innovative utilization of the firms human resource base and the building of a distinct organizational culture, financial resource capability, the innovative capabilities of the firm and hence strategy, ability of the firm to invest in systems and threatens continuity and sustainable development of the firm. These therefore hamper the longevity of the Finnish family-owned business. Considering the contribution of family-owned-business in Finland, the results of this study will inform policy makers on how these regulations affect the longevity of the Finnish family-owned business and how policy can be structured to aide family firms to achieve longevity in Finland.